2018
DOI: 10.1021/acs.iecr.8b02126
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Effect of Ceria on the Catalytic Performances of Ru/CeO2 Catalysts for Ammonia Synthesis

Abstract: Ru/CeO2 catalysts with different amounts of surface oxygen vacancies were prepared by changing the morphology of CeO2. The conversion of Ce4+ to Ce3+ and the formation of Ru–O–Ce bonds led to enhancement of the amount of oxygen vacancies. Ru species of low crystallinity enriched with Ru4+ ions exist on the surface of CeO2 nanorods, while metallic Ru particles exist on CeO2 nanocubes. The low crystallinity of Ru species and high concentration of oxygen vacancies enhanced the adsorption of hydrogen and nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 61 publications
8
95
1
Order By: Relevance
“…The peaks at v 0 (880.9 eV), v“ (885.3 eV), u 0 (898.9 eV), and u” (903.1 eV) are characteristic peaks of the Ce 3+ species, and the peaks at v (882.4 eV), v′′ (887.8 eV), v′′′ (897.6 eV), u (900.6 eV), u′′ (905.8 eV), and u′′′ (916.0 eV) are attributed to Ce 4+ species. The Ce 3+ concentration is related to the number of oxygen vacancies on the BaCeO 3 surface, which can be estimated from the area ratio of Ce 3+ peaks to Ce 4+ peaks . As shown in Table S3, the area ratio of Ce 3+ /Ce 4+ is 47.5 and 43.5 % for Ru/BaCeO 3 ‐a and Ru/BaCeO 3 ‐b, respectively, which indicates that Ru/BaCeO 3 ‐a has more surface oxygen vacancies than Ru/BaCeO 3 ‐b.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The peaks at v 0 (880.9 eV), v“ (885.3 eV), u 0 (898.9 eV), and u” (903.1 eV) are characteristic peaks of the Ce 3+ species, and the peaks at v (882.4 eV), v′′ (887.8 eV), v′′′ (897.6 eV), u (900.6 eV), u′′ (905.8 eV), and u′′′ (916.0 eV) are attributed to Ce 4+ species. The Ce 3+ concentration is related to the number of oxygen vacancies on the BaCeO 3 surface, which can be estimated from the area ratio of Ce 3+ peaks to Ce 4+ peaks . As shown in Table S3, the area ratio of Ce 3+ /Ce 4+ is 47.5 and 43.5 % for Ru/BaCeO 3 ‐a and Ru/BaCeO 3 ‐b, respectively, which indicates that Ru/BaCeO 3 ‐a has more surface oxygen vacancies than Ru/BaCeO 3 ‐b.…”
Section: Resultsmentioning
confidence: 98%
“…The Ce 3 + concentration is relatedt ot he number of oxygen vacancies on the BaCeO 3 surface, which can be estimated from the area ratio of Ce 3 + peaks to Ce 4 + peaks. [21] As shown in Table S3, the area ratio of Ce 3 + /Ce 4 + is 47.5 and 43.5 %f or Ru/BaCeO 3 -a and Ru/ BaCeO 3 -b, respectively,w hich indicates that Ru/BaCeO 3 -a has more surfaceo xygen vacancies than Ru/BaCeO 3 -b. In addition, we can further obtain from Ta bleS3, the area ratio of Ce 3+ /Ce 4 + for the twoc atalysts increased after Ru loading, which couldbec aused by thef ormation of more oxygen vacancies.…”
Section: Structure Analysismentioning
confidence: 91%
“…[111] In contrary to Ma et al studies, Lin et al, observed similar Ce 3 + /Ce 4 + ratio of~0.20 for both Ru/CÀ CeO 2 and Ru/RÀ CeO 2 , concluding decisive factors in the formation of oxygen vacancies is not Ce 3 + /Ce 4 + but particle size and chemical state of Ru species. [111] The Ru species in RÀ CeO 2 catalyst are merely crystalline and are majorly in oxide state (Ru n + ), while Ru particles in CÀ CeO 2 catalyst are metallic (Ru 0 ) in nature with large particle size. Presence of such RuÀ O species on Ru/RÀ CeO 2 -rod is beneficial for H 2 adsorption through formation of hydroxyl group, while oxygen vacancies enhance the N 2 adsorption and enhance NH 3 formation as seen from Figure 7.e.…”
Section: Oxidesmentioning
confidence: 73%
“…Studies show that concentration of oxygen vacancies is dependent on the morphology of the CeO 2 particles. [110] Rods(R), spherical(S) and cubic(C) shaped CeO 2 particles with (110), (111) and (100) exposing planes having similar size (100-300 nm) were synthesized by hydrothermal method. (Figure 7.b-d) The concentration of oxygen vacancies was related to the Ce 3 + /Ce 4 + ratio and are in the following order : Ru/RÀ CeO 2 (0.59) > Ru/C-À CeO 2 (0.46) > Ru/SÀ CeO 2 (0.32).…”
Section: Oxidesmentioning
confidence: 99%
“…that could supply electrons to metal, such as Ru, also facilitated ammonia synthesis ( Fig. 3 b) [47][48][49][50] .…”
Section: Thermocatalytic Ammonia Synthesismentioning
confidence: 99%